Microcalorimetry studies on the antibacterial effect of crude monkshood polysaccharide - Lin, Gui-mei (Zhejiang University Press, 2011)

(untitled)
In this paper, crude monkshood polysaccharide was isolated from Radix Aconiti Lateralis Preparata. The effects of crude monkshood polysaccharide on Escherichia coli and Staphylococcus aureus were investigated by microcalorimetry. The power-time curves of the bacterial growth at various concentrations (c) of crude monkshood polysaccharide were plotted with a TAM air isothermal microcalorimeter at 37 °C. The growth rate constant (μ), inhibitory ratio (I), peak-height (P (m)), and peak-time (t (m)) were calculated. From the data, the relationship between μ and c also was established. The growth rate constant μ decreased with the increasing concentrations of crude monkshood polysaccharide. Moreover, P (m) reduced and t (m) increased with increasing concentrations. The experimental results revealed that crude monkshood polysaccharide had inhibitory activity towards S. aureus and E. coli. Results obtained from our study strongly suggest that microcalorimetry is a fast, simple, and more sensitive technology that can be easily performed to study the effect of drugs on bacteria.